Understanding the Middle-Income Trap in ASEAN-4 Through GNI and Macroeconomic Indicators - Muhammad Khoirul Fuddin; Della Istikha Pramesti (Jurnal Economia, 2026)
This study aims to analyze the long-term and short-term effects of several independent variables (Portfolio Investment, Remittances, Exchange Rate, and Inflation) on GNI Per Capita to determine its effect on the middle-income trap condition. The research utilizes secondary data, specifically annual quantitative indicators from 1994 to 2023, sourced from the World Bank database. The sample consists of four ASEAN countries, namely Malaysia, Thailand, Indonesia, and the Philippines. The method used in the study was the analysis of the Vector Autoregressive (VAR) Vector Error Correction Model (VECM) panel. The results indicate that in the long term, investment portfolio, exchange rate, and inflation have a positive effect, while the remittance variable has no effect on real GNI Per Capita. In the short term, the exchange rate exerts a negative effect, while inflation shows a positive effect on GNI per capita in ASEAN-4. Conversely, portfolio investment and remittance do not exhibit short-term effects.